Penatalaksanaan Fisioterapi Pada Kondisi Osteoarthritis Genu Bilateral Di RSO Rof. DR. Soeharso Surakarta - Sugiyanti, Sugiyanti, Umi Budi Rahayu, S.Fis, M.Kes (2015)
Background: Osteoarthritis is a degenerative joint disease that is caused by a number of factors. This disease has a characteristic form of damage to the cartilage (cartilage). Abnormalities in OA of the knee joint cartilage damage that is contained subchondral followed thickening, osteophytes growth, damage to ligaments and joint capsule and are common signs of inflammation in the synovial causing effusion. Abnormalities that occur will cause clinical symptoms such as pain, joint stiffness, muscle weakness and impaired joint stability. Objective: To study about physiotherapy management in reducing pain, increasing range of motion, increase muscle strength and increase functional activity in the case of osteoarthritis genu bilateral using modalities Ultrasound (US) and Therapeutic Exercise (TL). Results: After treatment for 6 times obtained results of the assessment of pain in the right knee pain motion T1 : 31 mm to T6 : 20 mm and left knee T1 : 40 mm to T6 : 25 , an increase in knee flexor muscle strength right knee T1 : 4 to T6 : 4 , left knee T1 : 4 to T6 : 4 , an increase in knee extensor muscle strength right knee T1 : 4 to T6 : 4+ , left knee T1 : 4- become T6 : 4 , increased active range of motion right knee S : T1 : 0 -0-125 , became T6 : 0-0-130 , left knee S : T1 : 0-0-120 , became T6 : 0-0-125 , increase range of motion left knee passive S : T1 : 0-0- 130 , became T6 : 0-0-135 , left knee S : T1 : 0-0-125 , became T6 : 0-0-130 , the ability of functional activity up and down the stairs three trap on the right knee pain was reduced from T1 : 2 to T6 : 1 , left knee pain was reduced from T1 : 3 to T6 : 2 , and functional activity standing from a sitting position on the left knee pain decreased from T1 : 3 to T6 : 2. Conclusion : From the research that has been done, as evidenced by the use of modalities US and exercise therapy for 6 treatments associated with an increase impairment, functional limitation and disability. Key word : Osteoarthritis (OA), Ultra Sound (US) and Therapeutic Exercise (TL).